Plastic Waste Recycle for Industrial - Haryono, Muhammad Budi; Utami, Wikan Budi (Universitas PGRI Semarang, 2020)
The high-income countries are leading to higher consumption of plastic, despite prominent contribution to the global problem of plastic pollution. The high quantities of plastic wastes are extremely threatening to harm the environment and inhabitants due to mismanagement such as ingested in the fish and also harmful to human health (cancer is a major disease) if such consuming a fish. This review paper explored a solution to treating plastic waste to improve the sustainability of the environment. The use of recycled plastic wastes as a component has been found to be the most beneficial as it can be used to replace all solid components.